2022
DOI: 10.1128/aem.02513-21
|View full text |Cite
|
Sign up to set email alerts
|

Function and Application of the CRISPR-Cas System in the Plant PathogenErwinia amylovora

Abstract: Erwinia amylovora is an economically significant agricultural pathogen found throughout the world. In North America, E. amylovora has developed streptomycin resistance and therefore alternative treatments using phages have received increased attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The type I CRISPR system in E . amylovora was recently reported to be involved in resistance against invasive plasmids and not necessarily against phages [ 55 ]. No link has been identified to c-di-GMP regulation in this regard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The type I CRISPR system in E . amylovora was recently reported to be involved in resistance against invasive plasmids and not necessarily against phages [ 55 ]. No link has been identified to c-di-GMP regulation in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…CRISPR elements have been used in genotypically categorizing and tracking pathogenic evolution in E. amylovora [52][53][54]. The type I CRISPR system in E. amylovora was recently reported to be involved in resistance against invasive plasmids and not necessarily against phages [55]. No link has been identified to c-di-GMP regulation in this regard.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Among the group of strains, Bacillus megaterium , Bacillus aryabhattai , Erwinia spp. and Caballeronia glathei were excluded from further study, as they were previously reported to be potential plant pathogens ( Abdel-Monaim et al., 2012 ; Narsing Rao et al., 2019 , Dobritsa and Samadpour, 2019 , Parcey et al., 2022 ). A more detailed quantitative determination of bacterial phosphorus solubilization efficiency in liquid media (NBRIP) with different phosphorus contents showed that Rhizobium spp., Pantoea agglomerans , and Paenibacillus spp.…”
Section: Resultsmentioning
confidence: 99%
“…actinidiae ( Psa ) [ 50 ], Pseudomonas chlororaphis [ 51 ], Agrobacterium spp . [ 52 ], and Erwinia amylovora [ 53 ]. Regarding gene knockout, the ectopic expression of the type I-C CRISPR/Cas3 system from P .…”
Section: Discussionmentioning
confidence: 99%
“…actinidiae (Psa) [50], Pseudomonas chlororaphis [51], Agrobacterium spp. [52], and Erwinia amylovora [53]. Regarding gene knockout, the ectopic expression of the type I-C CRISPR/Cas3 system from P. aeruginosa in Pst DC3000 resulted in 67-92% efficiency of genome editing, characterized by large deletions (55-100 kb) at four target sites [25]; Application of CRISPR/SpCas9 in Psa generated very few transformants with one targeting sgRNA and 64.29% positive colonies carried 7.82-64 kb deletions.…”
Section: Plos Pathogensmentioning
confidence: 99%